Linking the scaling of tremor and slow slip near Parkfield, CA - Huang, H; Hawthorne, JC (Springer Nature, 2022)
There has been much debate about the fault zone processes that generate slow earthquakes, including tremor and slow slip. Indeed, we still debate whether tremor and slow slip are generated by the same process operating at different scales or by two distinct processes. Here we investigate tremor scaling near Parkfield, California; we examine how rupture duration scales with moment. We thoroughly search for and detect the low frequency earthquakes (LFEs) that constitute tremor and robustly estimate their durations. Our results show varying durations (0.1-0.6 s) and spectra for LFEs at the same location. These variations confirm a common assumption, that LFEs' observed low frequency contents are due to source processes, not path effects. The LFEs' amplitude and spectra variations are consistent with a linear moment-duration scaling: the same scaling observed among slow slip events. The similar scaling suggests that tremor and slow slip events are governed by the same fault zone process and that when we attempt to identify the process creating slow earthquakes, we should focus on processes which allow higher slip rates on smaller faults.